Usefulness of Flow Cytometric Analysis for Detecting Leptomeningeal Diseases in Non-Hodgkin Lymphoma - Shin, Sang-Yong (Ann Lab Med, 2016)
BACKGROUND: The clinical usefulness of flow cytometry (FCM) for the diagnosis of leptomeningeal diseases (LMD) in non-Hodgkin lymphomas has been suggested in previous studies but needs to be further validated. With this regards, we evaluated the use of FCM for LMD in a series of Korean patients with non-Hodgkin lymphoma. METHODS: FCM and cytomorphology were conducted using samples obtained from clinically suspected LMD patients, follow-up LMD patients, and those with high risk of developing tumorigenic diseases. We then compared results of FCM and cytomorphology. In total, 55 and 47 CSF samples were analyzed by FCM and cytomorphology, respectively. RESULTS: Of the samples analyzed, 25.5% (14/55) and 12.8% (6/47) were positive by FCM and cytomorphology, respectively. No samples were determined as negative by FCM but positive by cytomorphology. Seven patients were positive only by FCM and negative by cytomorphology, and six among them were clinically confirmed to have LMD either by follow-up cytomorphology or imaging study. CONCLUSIONS: We observed a high detection rate of tumor cells by FCM compared with cytomorphology. FCM study can be useful in early sensitive detection of LMD.